2017
DOI: 10.3892/mmr.2017.7718
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and preliminary analysis of circRNAs potentially involved in human intervertebral disc degeneration

Abstract: Circular RNAs (circRNAs) are relatively recently identified noncoding RNAs that are ubiquitously expressed in human tissues and serve key functions in regulating gene expression. However, few studies have focused on human intervertebral disc degeneration (IDD) circRNAs, and the potential role of circRNAs in IDD has not been described in detail. In the present study, circRNA expression data was downloaded from the Gene Expression Omnibus database, and circRNAs in the human intervertebral disc were classified ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…3A, B, C). There were also several reports demonstrated that circRNAs were actively participated in the metabolism process (Granados-Riveron and Aquino-Jarquin, 2016; Ye et al, 2015;Zou et al, 2017). For functional analysis, the DE genes at all the time points were searched in KEGG pathway database.…”
Section: The Functional Analysis Of the Parent Genes To Circrna Candimentioning
confidence: 99%
“…3A, B, C). There were also several reports demonstrated that circRNAs were actively participated in the metabolism process (Granados-Riveron and Aquino-Jarquin, 2016; Ye et al, 2015;Zou et al, 2017). For functional analysis, the DE genes at all the time points were searched in KEGG pathway database.…”
Section: The Functional Analysis Of the Parent Genes To Circrna Candimentioning
confidence: 99%
“…CircRNAs are ubiquitously expressed in human tissues, including human intervertebral disc tissue. 26 However, the specific function of most circRNAs in IVDD remains largely unclear. Using bioinformatics analysis, we have identified 503 DEcircRNAs between IVDD tissues and normal discs tissues using R language.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of circRNA in IDD remains unclear. To the best of our knowledge, only nine upregulated and nine downregulated circRNAs have been identified in degenerative NP samples compared with normal NP samples, and the functions of 12 of these dysregulated circRNAs remain fairly poorly understood ( 70 , 71 ). Using microarray data from the Gene Expression Omnibus (GEO) database, Zhu et al ( 72 ) predicted three circRNA-mediated regulatory pathways in IDD, namely, circRNA-102348/miR-185-5p/TGFB1/FOS, circRNA-102399/miR-302a-3p/HIF1A and circRNA-100086/miR-509-3p/MAPK1.…”
Section: Specificroles Of Circrna In Iddmentioning
confidence: 99%